Data collection on connected vehicles for road safety applications - Rocha, David Manuel Teixeira Alves da (2022)
The increasing growth of the automobile industry and the need of overusing personal vehicles amplifies problems directly related to road safety, such as the degradation of the quality of the roads, the increase in volume of the automobile flow, and through the addition of dangerous weather events caused by climate change. To alleviate these emerging problems, intelligent cooperative communication systems (C-ITS) and Internet of Things (IoT) solutions emerge, allowing the overcome of human and local sensory systems limitations through the collection and distribution of relevant data in connected vehicles, which is fundamental in finding solutions that transform the concept of Smart Cities into reality. This dissertation implements an intra- and inter-vehicle sensory data collection system, starting with the acquisition of relevant data present on the CAN bus, collected through the vehicle’s OBD-II port and external sensors. Use is made of short-range communications such as Bluetooth-Low-Energy (BLE), Vehicle-to-Vehicle (V2V) and Vehicle-to-Infrastructure (V2I) in conjunction with long-range cellular communications (LTE/5G). Data access endpoints are provided through an API and a MQTT broker. At last, logging methods are developed to allow conscious debugging of these systems, as well as to evaluate timing restrictions. The results of the experimental tests carried out reveal the usefulness of the acquired data, which allows the realization of detailed longitudinal analyzes of dangerous roads, as well as notifying, in near real-time, adverse road conditions to drivers. Therefore, the data collection system developed reveals itself as a potentially valuable tool for providing useful information both to competent authorities and to the common population, as a method to improve road safety.